Randomized clinical trial: Long-term Staphylococcus aureus decolonization in patients on home parenteral nutrition. Issue 5 (May 2023) - Gompelman, Michelle; Wezendonk, Guus T.J.; Wouters, Yannick; Beurskens-Meijerink, Judith; Fragkos, Konstantinos C.; Rahman, Farooq Z.; Coolen, Jordy P.M.; van Weerdenburg, Ingrid J.M.; Wertheim, Heiman F.L.; Kievit, Wietske; Akkermans, Reinier P.; Serlie, Mireille J.; et al.
Summary: Background & aims: Staphylococcus aureus decolonization has proven successful in prevention of S. aureus infections and is a key strategy to maintain venous access and avoid hospitalization in patients receiving home parenteral nutrition (HPN). We aimed to determine the most effective and safe long-term S. aureus decolonization regimen. Methods: A randomized, open-label, multicenter clinical trial was conducted. Adult intestinal failure patients with HPN support and carrying S. aureus were randomly assigned to a 'continuous suppression' (CS) strategy, a repeated chronic topical antibiotic treatment or a 'search and destroy' (SD) strategy, a short and systemic antibiotic treatment. Primary outcome was the proportion of patients in whom S. aureus was totally eradicated during a 1-year period. Secondary outcomes included risk factors for decolonization failure and S. aureus infections, antimicrobial resistance, adverse events, patient compliance and cost-effectivity. Results: 63 participants were included (CS 31; SD 32). The mean 1-year S. aureus decolonization rate was 61% (95% CI 44, 75) for the CS group and 39% (95% CI 25, 56) for the SD group with an OR of 2.38 (95% CI 0.92, 6.11, P  = 0.07). More adverse effects occurred in the SD group ( P  = 0.01). Predictors for eradication failure were a S. aureus positive caregiver and presence of a (gastro)enterostomy. Conclusion: We did not demonstrate an increased efficacy of a short and systemic S. aureus decolonization strategy over a continuous topical suppression treatment. The latter may be the best option for HPN patients as it achieved a higher long-term decolonization rate and was well-tolerated (NCT03173053).